Pulmonary adenofibroma: Cytologic and clinicopathologic features of a rare benign primary lung lesion. Issue 11 (30th May 2012) - Vitkovski, Taisia; Zeltsman, David; Esposito, Michael; Morgenstern, Nora
<x xml:space="preserve">Abstract</x> We report a case of pulmonary adenofibroma in a 29‐year‐old female found by CT scan during work‐up for midline chest pain. To our knowledge, the cytological features of this entity have not been previously reported. Cytology demonstrated bland epithelial and stromal cells of varying size without karyorrhexis, pyknosis, or necrosis and with very rare mitoses. Stromal cells were present as either naked bipolar nuclei, as spindle cells with fragile eosinophilic cytoplasm, or as rare larger carrot shaped nuclei. Epithelial cells were present as small loosely cohesive groups with smooth round nuclei and moderate amounts of cytoplasm. Histologically, this lesion consisted of a leaf‐like fibroepithelial pattern in which the clefts were lined by a single layer of cuboidal epithelium reminiscent of adenofibroma occurring in the female genital tract. Immunohistochemical analysis demonstrated epithelium that stained positively for pan‐cytokeratin and TTF‐1. The stroma stained positively for vimentin and desmin, and was weakly positive for SMA‐1. The lesion was confirmed to be pulmonary adenofibroma with a smooth muscle component. The differential diagnosis for this lesion includes, but is not limited to, pulmonary hamartoma, pulmonary blastoma, adenomyofibroma, synovial sarcoma, and visceral metastases. It is important for cytopathologists to be aware of this benign entity because it can be encountered on lung FNA specimens. Considering this benign lesion in the differential diagnosis may help plan for minimal lung resection. Confirmatory intraoperative frozen section is a reasonable option. Diagn. Cytopathol. 2013;41:991–996. © 2012 Wiley Periodicals, Inc.